Analysis of Mathematical Connection Ability on Gender Differences of Junior High School Students - Nisa, Nastiti Khairun; Dewanti, Sintha Sih (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The purpose of this study is to analyze the ability of mathematical connections to gender differences. A total of 92 grade VII students of SMP N 3 Bantul became the subject of this study. This type of research is descriptive quantitative research. The research instrument uses mathematical connection ability test questions with three indicators, namely connecting concepts between mathematics, connecting mathematical concepts with other fields of science and connecting mathematical concepts with everyday life. The data collection technique is using a test technique. The data obtained was then given a score and then analyzed and conclusions were drawn. The results of the study showed that there were differences in the mathematical connection abilities between male and female students where the female students' mathematical connection abilities were superior to male students.